Studi Pemanfaatan Rumput Liar Pekarangan Rumah sebagai Bahan Baku Pembuatan Ekoenzim - Syafriadi, Riko; Nizar, Umar Kalmar; Stiadi, Della Rosalynna; Zuyyina, Himla; Fitriani, Fitriani; Fika, Miva Hemalia; Fadhila, Radhiatul; Syafri, Vanny Sofiana (Periodic, 2025)
Wild grass is a plant that grows unwanted in certain areas such as fields, gardens, agricultural land and yards. This plant is generally discarded and rarely used. Based on the composition of the materials used in ecoenzymes, fresh wild grass plants have great potential to be used as raw materials for ecoenzymes. This study aims to determine the characteristics of ecoenzymes produced using wild grass from home gardens, such as fragrant nutsedge (Cyperus aromaticus var. Elatus), virginica grass (Leersia virginica), Belulang grass (Eleusine indica), Peking grass (Agrostis stolonifera) and Ilalang (Imperata cylindrica). Wild grass with a certain composition is mixed with brown sugar and water in a ratio of 3: 1: 10 in five containers. The ecoenzyme manufacturing process is carried out for 90 days and changes in color, odor, and pH of the ecoenzyme product are observed. The results of this study indicate that the color of the five ecoenzymes produced shows a change in color to become more cloudy than the initial color of the ecoenzyme. The odor of the five ecoenzymes produced showed a change in odor to become more sour in the third month like the typical odor of weeds. Meanwhile, the pH of the ecoenzymes produced ranged from 5.8 to 7.8. The high pH of the ecoenzymes produced was caused by the low organic acid content of the ecoenzymes produced. In addition to observing the physical condition and pH of the ecoenzymes produced, qualitative testing of the nutrient content in the form of N, P and K was also carried out. Testing of the nutrient content of N, P and K carried out showed that the ecoenzymes produced from home yard weeds contained the nutrients N, P and K. These results indicate that the ecoenzymes produced can also be used as liquid organic fertilizers